2021
DOI: 10.1002/lt.25985
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia in Children With End‐Stage Liver Disease on the Transplant Waiting List

Abstract: Sarcopenia predicts morbidity and mortality in adults with end-stage liver disease (ESLD) and is determined by total psoas muscle area (tPMA) measurement from computed tomography (CT) imaging. Recently developed pediatric age-and sex-specific tPMA growth curves provide the opportunity to ascertain the prevalence and impact of sarcopenia in children awaiting liver transplantation (LT). We performed a retrospective single-center study to evaluate sarcopenia in children with ESLD between 1 and 16 years of age wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(78 citation statements)
references
References 63 publications
2
66
0
Order By: Relevance
“…43 In children with end-stage liver disease, sarcopenia has been associated with adverse outcomes including growth failure, hospitalizations, infections, and motor delay. 151,155,156 Sarcopenic Obesity Sarcopenic obesity refers to the state of decreased muscle mass in the setting of increased fat mass. This phenotype presents a unique clinical challenge in that it can be difficult to detect without dedicated testing because fat mass can mask underlying muscle wasting.…”
Section: Accepted Articlementioning
confidence: 99%
“…43 In children with end-stage liver disease, sarcopenia has been associated with adverse outcomes including growth failure, hospitalizations, infections, and motor delay. 151,155,156 Sarcopenic Obesity Sarcopenic obesity refers to the state of decreased muscle mass in the setting of increased fat mass. This phenotype presents a unique clinical challenge in that it can be difficult to detect without dedicated testing because fat mass can mask underlying muscle wasting.…”
Section: Accepted Articlementioning
confidence: 99%
“…This study aimed to determine the relation between body metrics (PMI and SMI as measurements of sarcopenia, and ScFI as measurement of subcutaneous fat storage) derived from preoperative abdominal CT scans and postoperative short-term clinical outcomes and complications in children with cirrhotic liver disease undergoing LT. While these body metrics are advocated in adults for predicting postoperative outcomes (4,10), in children studies on tPSMA and PMI have shown varying results, and SMI and ScFI have not been previously studied (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that psoas muscle index (PMI), skeletal muscle index (SMI), and fat indices could be reliably determined even in young children (median age 4.6 months) with biliary atresia (13). Recent pediatric studies have also shown potential clinical application for PMI and total psoas muscle surface area (tPMSA), but did not investigate SMI or fat indices (14)(15)(16)(17). In adults undergoing LT, sarcopenia diagnosed by CT-based body metrics is advocated as an independent predictor of higher waiting list and posttransplantation mortality, and higher perioperative complication rates (18,19).…”
mentioning
confidence: 99%
“…(3) accordingly, successful KP could contribute to save organs in the context of worsening donor shortage; and (4) even in those children where KP does not provide reversal of cholestasis and in whom LT will be eventually required, partial biliary drainage may allow to buy months and sometimes years with prolonged preservation of general and nutritional status, contributing to reduce the risks of LT (39). Data from single-center studies, as well as national or multicenter registries, reported that the 20-year native liver survival (NLS) rate after the Kasai operation ranges between 14 and 44% (12)(13)(14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%